A stacked Yagi antenna for APT reception - GUPTA, J. DAS (MAUSAM, 1971)
The paper describes design and construction of an antenna system with two Yagi arrays stacked to have high gain and directivity. The antenna can be rotated both in azimuth and elevation and used to track a weather satellite by remote control using torque drive motors.